VD_FINDINFO Arrêt / 2012 / 815 vom 3. Oktober 2012 - VD Tribunal cantonal (2012)
TUTELLE, CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION, ALCOOLISME | 370 CC, 392 ch. 1 CC, 393 ch. 2 CC, 393 CPC, 489 CPC